Revised Use Case Point Method - Effort Estimation in Development Projects for Business Applications - Frohnhoff, Stephan; Engels, Gregor (Setting Quality Standards, Proceedings of the 11th International Conference on Quality Engineering in Software Technology (CONQUEST 2008), Potsdam (Germany))
Rapid and precise effort estimation of software development projects is crucial in IT industry. In a case study, the Use Case Point (UCP) method was applied to 15 commercial software development projects. The estimated efforts were compared with the incurred project efforts. We measured a standard deviation of 42 %. This is not acceptable for industrial usage. Therefore, we propose appropriate improvements of the Use Case Point method leading to significantly higher estimation accuracy with only 20 % standard deviation. The contribution of this paper is a detailed description of the improved Use Case Point method.

Coherent optoelectronics with single quantum dots - Zrenner, Artur; Ester, P; Michaelis de Vasconcellos, S; Hübner, M C; Lackmann, L; Stufler, S; Bichler, M (Journal of Physics: Condensed Matter)
The optical properties of semiconductor quantum dots are in many respects similar to those of atoms. Since quantum dots can be defined by state-of-the-art semiconductor technologies, they exhibit long-term stability and allow for well-controlled and efficient interactions with both optical and electrical fields. Resonant ps excitation of single quantum dot photodiodes leads to new classes of coherent optoelectronic functions and devices, which exhibit precise state preparation, phase-sensitive optical manipulations and the control of quantum states by electrical fields.

Quasar Enterprise - Engels, Gregor; Voß, Markus (Informatik-Spektrum)
Die Gestaltung und Weiterentwicklung großer Anwendungslandschaften gilt heutzutage als eine der größten Herausforderungen in der Softwaretechnik. Als Lösungsansatz wurde in den letzten Jahren vielfach das Paradigma einer serviceorientierten Architektur (SOA) diskutiert und insbesondere durch herstellerspezifische Technologien unterstützt. Dieser Beitrag widmet sich einer häufig vernachlässigten methodischen Herangehensweise und stellt mit Quasar Enterprise einen strukturierten und in der Praxis erprobten Lösungsansatz vor. Insbesondere werden konkrete Verfahrensbausteine für eine durchgängige Methode vorgestellt, die einem Architekten helfen, eine auf das zu unterstützende Geschäft ausgerichtete Anwendungslandschaft zu entwickeln und zu warten. Wesentliche Charakteristika von Quasar Enterprise sind der konsequente Einsatz einer serviceorientierten Herangehensweise, die Verwendung eines Architektur-Frameworks als Strukturierungsgrundlage und die Aufbereitung der Methode in Form von 20 Verfahrensbausteinen.

Theoretical and experimental investigations of Coulomb blockade in coupled quantum dot systems - Kaiser, F J; Kohler, S; Hänggi, P; Malecha, M; Ebbecke, J; Wixforth, A; Schumacher, H W; Kästner, B; Reuter, Dirk; Wieck, A D (Journal of Physics: Condensed Matter)

Molecular dynamics simulation of defect formation and precipitation in heavily carbon doped silicon - Zirkelbach, F.; Lindner, Jörg; Nordlund, K.; Stritzker, B. (Materials Science and Engineering: B)
The precipitation process of silicon carbide in heavily carbon doped silicon is not yet fully understood. High resolution transmission electron microscopy observations suggest that in a first step carbon atoms form C Si dumbbells on regular Si lattice sites which agglomerate into large clusters. In a second step, when the cluster size reaches a radius of a fewnm, the high interfacial energy due to the SiC/Si lattice misfit of almost 20% is overcome and the precipitation occurs. By simulation, details of the precipitation process can be obtained on the atomic level. A recently proposed parametrization of a Tersoff-like bond order potential is used to model the system appropriately. Preliminary results gained by molecular dynamics simulations using this potential are presented.

Editorial: XXI. Messtechnisches Symposium des Arbeitskreises der Hochschullehrer für Messtechnik (AHMT), Paderborn, 20.--22.09.2007 - Henning, Bernd (Technisches Messen)

Theoretical study of the localization of excess electrons at the surface of ice - Hermann, A; Schwerdtfeger, P; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)

Mancosu, Paolo, “Mathematical Explanation: Problems and Prospects”, In: Topoi 20 (2001), 97–117 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Sprachen im Konflikt: Zur diskursiven Reflexion der Galizischen Polyglossie in Lemberger Zeitungen des ausgehenden 19. Jahrhunderts - Ptashnyk, Stefaniya (Deutsch in multilingualen Stadtzentren Mittel- und Osteuropas. Um die Jahrhundert-wende vom 19. zum 20. Jahrhundert)

Significance of individuation in adult child-parent relationships - Buhl, Heike M. (Journal of Family Issues)
This study investigates the significance of adult children's individuation for the adult child—parent relationship. Following Youniss, individuation was assessed via its dimensions of both connectedness and individuality. A sample of 349 participants between 20 and 47 years of age were given questionnaires containing scales from the Network of Relationships Inventory among others. Individuation predicted satisfaction, intimacy, and conflict. The combination of connectedness and individuality did not have any impact on relationship quality. The significance of children's individuation did not differ between young and middle-aged adults.

20 Blicke auf das Jesuskind. Zum 100. Geburtstag von Olivier Messiaen (1908-1992) - Schroeter-Wittke, Harald (Praktische Theologie)

Editor of a special issue on "ICTs and Society: PhD Students' Transdisciplinary Research Projects" (Proceedings of the PhD conference “ICTs and Society“, June 20-21, 2008, University of Salzburg) - Fuchs, Christian (triplec (Cognition, Communication, Co- operation))

Wie Backfische schreiben: Zur Wechselwirkung von gesellschaftlichem Diskurs und authentischem Schreiben von Mädchen und jungen Frauen in der ersten Hälfte des 20. Jahrhunderts - Schuster, Britt-Marie (Bausteine zu einer Geschichte des weiblichen Sprachgebrauchs VIII. Sprachliches Agieren von Frauen in approbierten Textsorten. Internationale Fachtagung. Magdeburg 10.–11.09. 2007)
Keywords: Kommunikationsgeschichte

„Same, Same But Different": Zur Bedeutung und zum Wandel von Image in der Popkultur postmoderner Mediengesellschaften. - Jacke, Christoph (Medien und Imagepolitik im 20. Jahrhundert. Deutschland, Europa, USA.)

Distributed Computing in Sensor Systems, Third IEEE International Conference, DCOSS 2007, Santa Fe, NM, USA, June 18-20, 2007, Proceedings

Flexible dezentrale Administration überschneidender Benutzergruppen – Informationelle Selbstbestimmung durch benutzerkontrollierte Provisionierung - Brennecke, Andreas; Finke, Stefan; König, J.; Oevel, Gudrun (Konferenzband der 20. DFN-Jahrestagung DFN2006)

Konzipierung selbstoptimierender Systeme am Beispiel eines magnetischen Linearantriebs - Gausemeier, Jürgen; Frank, Ursula; Pook, Sebastian; Zimmer, Detmar; Schmidt, Alexander

KnowledgeBus - An Architecture to Support Intelligent and Flexible Knowledge Management - Mlynarski, Michael; Hinkelmann, Knut; Magenheim, Johannes; Nelkner, Tobias; Reinhardt, Wolfgang; Holzweissig, Kai (Creating New Learning Experiences on a Global Scale, Second European Conference on Technology Enhanced Learning, EC-TEL 2007, Crete, Greece, September 17-20, 2007)

Semivirtuelle Lernumgebung zum wissenschaftlichen Arbeiten als Ergänzung des Studienangebots der Universität Augsburg - Heinze, Nina; Sporer, Thomas; Jenert, Tobias (Deutsche Gesellschaft für Informationswissenschaft und Informationspraxis: Tagungen der Deutschen Gesellschaft für Informationswissenschaft und Informationspraxis)
Keywords: Wissenschaftliches Arbeiten; Blended Learning; Tutoring

Charge and spin dynamics in a two-dimensional electron gas - Pugžlys, A; Rizo, P J; Ivanin, K; Slachter, A; Reuter, Dirk; Wieck, A D; Wal, C H van der; Loosdrecht, P H M van (Journal of Physics: Condensed Matter)

IRIS (1978-2006) Historical Reflection through Visual Analysis - Molka-Danielsen, Judith; Trier, Matthias; Shlyk, Vadim; Bobrik, Annette; Nurminen, Markku I. (Proceedings of IRIS30, Tampere, 2007)
IRIS (Information Systems Research in Scandinavia) Conference is an annual meeting for researchers in Scandinavia. Through 29 annual conference meetings a social network of co-authorships and general research collaboration has emerged. This article contributes a historical reflection and analysis of the social network of researchers associated with the IRIS in the period from 1978 to 2006. We make use of the network visualization and analysis tool called Commetrix. We will examine the influence of certain researchers in this network by identifying their betweenness centrality and degree centrality. We will reflect on the nature and characteristic of the research topics by analyzing the network of keywords found in the conference paper titles, and visualizing their representation in the network.

En route vers un but commun: Besonderheiten der Kommunikation zwischen Sprachlernern und Implikationen für die Fremdsprachendidaktik. - Behrent, Sigrid (Band zur Tagung: Multilateralität und europäischer Bildungsauftrag, Bremen (20.-22. Juni 2006))

„In diesem Schein des Bekannten liegt das ganze Geheimniß des Volkstons“ – Die Dichtung der Heidelberger Romantik in der Musik - Tumat, Antje (200 Jahre Heidelberger Romantik)
Die Dichtung der sogenannten „Heidelberger Romantik“ entfaltete ihre geistesgeschichtliche Wirkung in hohem Maße durch ihre musikalische Rezeption. Die Volksliedsammlung Des Knaben Wunderhorn 2 wurde von Achim von Arnim und Clemens Brentano ohne Notenbeigabe herausgegeben; bis ins 20. Jahrhundert reizten ihre Texte immer wieder zu Kompositionen, von denen die Wunderhorn-Lieder Gustav Mahlers heute die Bekanntesten sind.3 Die inhaltliche Heterogenität der Sammlung spiegelt sich in der Geschichte ihrer Vertonungen: Die verschiedenen Texte tragen einerseits Angebote zur kollektiven Identifikation, beispielsweise im nationalen Sinne, in sich. Gleichzeitig vermögen sie andererseits ein solches kollektives Identifikationsangebot zu durchkreuzen, indem sie das Leiden an der Außenseiterrolle — etwa in der Person eines Fahnenflüchtlings4 — thematisieren, wie in den von Gustav Mahler gewählten, zumeist von starker Gebrochenheit getragenen Liedern. Die Gestalt der Texte in der Sammlung sollte nach der Bearbeitung durch die beiden Herausgeber dem entsprechen, was sie unter „Volkston“ verstanden.5 Dieser „Ton“ der Texte wurde wiederum in der Folgezeit als verbürgter Volkston rezipiert. Er beeinflusste Dichter wie Joseph von Eichendorff, dessen Lyrik von der Wunderhorn-Sammlung inspiriert wurde.6 Das Heidelberger Jahr 1807/08, in dem dieser die Liedsammlung kennenlernte, war für Eichendorff „eines der entscheidendsten seines Lebens“.7 Die literarische Rezeption der Wunderhorn-Texte in seiner Lyrik fand wiederum ihrerseits in unzähligen Vertonungen musikalischen Widerhall, so etwa in Robert Schumanns Liederkreis op. 39.8

NOW: Theologische Zugänge zu einer popkulturellen Kategorie - Schroeter-Wittke, Harald (Pop Insights. Bestandsaufnahmen aktueller Pop- und Medienkultur)

Simulation of the hydrodynamic drag of aggregated particles - Binder, Christian; Feichtinger, Christian; Schmid, Hans-Joachim; Thürey, Nils; Peukert, Wolfgang; Rüde, Ulrich (Journal of Colloid and Interface Science)
The drag force on aggregates and partially sintered agglomerates is assessed using the lattice Boltzmann method (LBM) and accelerated Stokesian dynamics (ASD). Both methods have been compared in terms of accuracy and computational effort. It is shown that they give comparable results if all numerical parameters are controlled carefully. LBM requires a much higher computational effort, however, in contrast to ASD it is able to simulate partially sintered agglomerates as well. The results show that even a very small amount of sintering leads to a significant reduction in the drag force. The analysis of the drag force on agglomerates as well as on aggregates shows that there is no simple geometric quantity which is uniquely related to the drag force. Moreover, there is a significant variation in drag force for single aggregates at different orientations or for the orientation averaged drag force of different aggregates of the same size. This is explained by the structural effects which may lead to a variation in the drag force up to +-20%.

Foundations of Formal Sciences IV. The History of the Concept of Formal Sciences

Das Gedächtnis der Literatur. Konstitutionsformen des Vergangenen in der Literatur des 20. Jahrhunderts

Der Kult der Arbeit als Ausgangspunkt für das neue menschliche Gemeinwesen der Zukunft. Émile Zolas „Le Travail“: Ein Urbild des Städtebaus im 20. Jahrhundert - Seng, Eva- Maria (Dimensionen der Politik: Aufklärung, Utopie, Demokratie. Festschrift für Richard Saage zum 65. Geburtstag)

„Im Kopf die Toten verwesen nicht“. Werner Fritschs „Theater des Todes“ - Eke, Norbert Otto (Zeitschrift für deutsche Philologie 125, Sonderheft: Das Gedächtnis der Literatur. Konstitutionsformen des Vergangenen in der Literatur des 20. Jahrhunderts)

Das Gedächtnis der Literatur. Zur Einführung - Eke, Norbert Otto; Allkemper, Alo (Zeitschrift für deutsche Philologie 125, Sonderheft: Das Gedächtnis der Literatur. Konstitutionsformen des Vergangenen in der Literatur des 20. Jahrhunderts)

A fast k-means implementation using coresets - Frahling, Gereon; Sohler, Christian (Proceedings of the twenty-second annual symposium on Computational geometry - SCG '06)
In this paper we develop an efficient implementation for a k-means clustering algorithm. Our algorithm is a variant of KMHybrid [28, 20], i.e. it uses a combination of Lloyd-steps and random swaps, but as a novel feature it uses coresets to speed up the algorithm. A coreset is a small weighted set of points that approximates the original point set with respect to the considered problem. The main strength of the algorithm is that it can quickly determine clusterings of the same point set for many values of k. This is necessary in many applications, since, typically, one does not know a good value for k in advance. Once we have clusterings for many different values of k we can determine a good choice of k using a quality measure of clusterings that is independent of k, for example the average silhouette coefficient. The average silhouette coefficient can be approximated using coresets.To evaluate the performance of our algorithm we compare it with algorithm KMHybrid [28] on typical 3D data sets for an image compression application and on artificially created instances. Our data sets consist of 300,000 to 4.9 million points. We show that our algorithm significantly outperforms KMHybrid on most of these input instances. Additionally, the quality of the solutions computed by our algorithm deviates less than that of KMHybrid.We also computed clusterings and approximate average silhouette coefficient for k=1,…,100 for our input instances and discuss the performance of our algorithm in detail.

Transaktionshäufigkeit als Indikator für die Angebotsgestaltung bei deutschen Online-Brokern. 45 (1), 20-38. - Kundisch, Dennis; Krammer, A. (Der Markt - Zeitschrift für Absatzwirtschaft und Marketing)

Tactile sensors for determination of elastic properties of brain tissue mimicking phantoms - Kehl, Romina; Stroop, Ralf; Oliva Uribe, David; Hemsel, Tobias; Henning, Bernd
In spite of the outstanding importance of neuronavigational techniques the neurosurgeon has still highly to rely on his visual as well as tactile sense and his experience in distinguishing tumor tissue from intact brain parenchyma. All the more - as neuronavigation is based on preoperative imaging scans - considerable brain shift may occur during surgery and that will lead to erroneous results. Furthermore the surgeon loses his tactile sense during endoscopic surgery. Therefore control of tissue manipulation is limited today to the fiberoptic image techniques, possibly ensured by neuronavigational supervision or haptic feedback systems. In robotic guided surgery the missing tactile sensing will be particularly crucial. The human sense of touch is a highly complex sensory perception comprising epicritical and propiozeptive information processing. The development of a tool for intraoperative tactile perception will be a highly challenging task to improve the safety during surgery. Different sensor concepts (elasticity probe and resonant piezoelectric sensor) have been set up and adapted to distinguish elasticity differences in soft tissue mimicking gel phantoms. The elasticity probe is based on two leaf springs of different bending stiffness. The two tips of the beams act both on the material to be tested. The two deflections measured by strain gauges are processed in a mathematical model calculating the phantoms' stiffness. In contrast to this differential sensing concept the piezoelectric sensor, which is driven at its resonance, measures stiffness and damping of the phantoms by evaluating frequency or phase shift and amplitude change. Gelatine gels of different concentrations (5{%}, 10{%}, 20{%} of gelatine) have been used for a characterization of sensor elements and their sensitivity to elasticity distinctions. Using the hand-guided elasticity probe the determination of gel elasticity is performed with high reliability. By constant mechanical load the piezoelectric sensor also presents a proportional dependency of tissue elasticity.

3. Workshop der GI-Fachgruppe "Didaktik der Informatik", 19.-20. Juni 2006 an der Universität Potsdam

Cassini, Alejandro, “Newton and Leibniz on Non-substantial Space”, In: Theoria. Segunda Epoca 20, Nr. 52 (2005), 25-42 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

"Die Ringe des Saturn": Ein kosmologisches Strukturmodell für W.G. Sebalds Lektüre zivilisatorischer Abirrungen - Öhlschläger, Claudia (Gestirn und Literatur im 20. Jahrhundert)

Gestalttherapie als sonderpädagogische Herausforderung an die Ausbildung von SonderpädagogInnen - Laubenstein, Désirée (In: Behinderte in Familie, Schule und Gesellschaft, 29. Jahrgang, Nr. 2, Praxisteil)

Performance of 20 Gb/s quaternary intensity modulation based on binary or duobinary modulation in two quadratures with unequal amplitudes - Ibrahim, Selwan K.; Bhandare, Suhas; Noé, Reinhold (IEEE JOURNAL OF SELECTED TOPICS IN QUANTUM ELECTRONICS)

20-Gb/s quaternary intensity modulation based on duobinary modulation with unequal amplitude in two polarizations - Ibrahim, Selwan K.; Bhandare, Suhas; Noé, Reinhold (IEEE PHOTONICS TECHNOLOGY LETTERS)

20-Gb/s quaternary intensity modulation based on duobinary modulation with unequal amplitude in two polarizations - Ibrahim, Selwan K.; Bhandare, Suhas; Noé, Reinhold (IEEE PHOTONICS TECHNOLOGY LETTERS)

A flexible testbed for the rapid prototyping of MIMO baseband modules - Ramírez, D.; Santamaría, I.; Pérez, J.; Vía, J.; Tazón, A.; Garcia-Naya, J. A.; Fernandez-Carames, T. M.; Lopez, M. Gonzalez; Iglesias, H. J. Pérez; Castedo, L. (Proc. Int. Symp. on Wireless Comm. Systems)
Hardware platforms and testbeds are an essential tool to evaluate, in realistic scenarios, the performance of Multiple-Input-Multiple-Ouput (MIMO) systems. In this work we present a simple and easily reconfigurable $2 × 2$ MIMO testbed for the rapid prototyping of the signal processing baseband functions. The signal generation module consists of a host PC equipped with a board that contains two high performance 100 MHz DACs and a 1 GB memory module that allows the transmission of extremely large frames of data. At the receiver side, we use another host PC equipped with two 105 MHz ADCs, another 1 GB memory module and a trigger that starts the acquisition process when the presence of signal is detected. The platform has been designed to operate at the ISM band of 2.4 GHz with a RF bandwidth of 20 MHz. In order to minimize the number of DAC and ADC circuits, signals are generated and acquired at an IF of 15 MHz. Upconversion to RF is performed with two RF vectorial signal generators (Agilent E4438C) and downconversion with two specific circuits designed from commercial components. Transmitter and receiver signal processing functions are implemented off-line in Matlab. To illustrate the performance and capabilities of the platform, we present the results of two experiments of a $2 × 2$ MIMO transmission with Alamouti coding.

"Über den Werth des Sokrates als Philosophen". Einige Anmerkungen zu Schleiermacher und Kierkegaard - Janus, Richard (Schleiermacher und Kierkegaard. Subjektivität und Wahrheit)

Neue Orientierungen der Ernährungs- und Verbraucherbildung - Schlegel-Matthies, Kirsten (Aktuelle Aspekte in der Ernährungsbildung und -beratung. Tagungsband der DGE-Arbeitstagung am 29. und 30. September in Paderborn)

Corpora in Applied Linguistics - Mindt, Ilka; Hunston, Susan (ICAME Journal 29, Computers in English Linguistics)

Preparation of electron waveguide devices on GaAs/AlGaAs using negative-tone resist calixarene - Knop, M; Richter, M; Maßmann, R; Wieser, U; Kunze, U; Reuter, Dirk; Riedesel, C; Wieck, A D (Semiconductor Science and Technology)

Besonderheiten und Wettbewerbsprobleme des Marktes für wissenschaftliche Fachzeitschriften - Haucap, Justus; Hartwich, Tobias; Uhde, André (Vierteljahrshefte zur Wirtschaftsforschung)
ie Preise für wissenschaftliche, technische und medizinische (WTM) Fachzeitschriften sind in den letzten 20 Jahren dramatisch gestiegen. Die unterschiedlichen Preisentwicklungen zwischen kommerziellen und nichtkommerziellen Verlagen ist dabei nicht durch unterschiedliche Kostenentwicklungen zu erklären. Vielmehr haben die forschungsorientierten Top-Journale Marktmacht, da sie den Charakter positionaler Güter haben, die von Bibliotheken nur sehr schwer substituiert werden können, sodass streng genommen aufgrund der Einzigartigkeit jedes einzelnen Artikels jede Top-Zeitschrift einen eigenen Markt konstituiert. Top-Zeitschriften haben aus drei Gründen einen erheblichen Preissetzungsspielraum: Erstens sind der Markteintritt und die Ablösung teurer Top-Journale aufgrund des Koordinationsproblems zwischen Autoren, Gutachtern und Bibliotheken für neue Zeitschriften sehr schwierig. Zweitens haben Bibliotheken Wechselkosten (durch die Tendenz, vollständige Reihen zu beziehen). Drittens ist die Nachfrage auch aufgrund der kollektiven Entscheidungsfindung in Bibliotheken relativ unelastisch. Ein effektiver Ausweg, der die Verlage disziplinieren würde, könnte die konzertierte Aktion von Forschungsgemeinschaften sein, die ihre Mitarbeiter oder die von ihnen finanziell geförderten Wissenschaftler verpflichten, ihre Artikel und Forschungsergebnisse kostenfrei oder zumindest zu günstigen Konditionen zur Verfügung zu stellen.

Kang, Jinho, “On the Composition of the Prototractatus”, Philosophical Quarterly 55 (2005), 1–20 - Peckhaus, Volker (Mathematical Reviews)

Refinement and Consistency in Multiview Models - Wehrheim, Heike (Language Engineering for Model-Driven Software Development, 29. February - 5. March 2004)

Götter in der Stadt oder: „Wo Aas ist, sammeln sich die Geier!“ Stadtuntergänge bei Brecht und Trolle - Eke, Norbert Otto (Mahagonny.com. The Brecht Yearbook 29)

Considerations for the Calculation of Greenhouse Gas Reduction by Photovoltaic Solar Energy - Krauter, Stefan; Rüther, R. (Renewable Energy Vol. 29, Issue 3 (2004), S. 345–355.)

Renewable Energies in Latin America - Krauter, Stefan (Proceedings of the Second World Renewable Energy Forum, Eurosolar, Bonn (Deutschland), 29.–31. Mai 2004)

Dual-gate GaAs/AlGaAs quantum point contact with tuneable subband energy separation - Kähler, D; Knop, M; Kunze, U; Reuter, Dirk; Wieck, A D (Semiconductor Science and Technology)

„Liebe geht durch den Magen“: Mahlzeit und Familienglück im Strom der Zeit - Schlegel-Matthies, Kirsten (Die Revolution am Esstisch. Neue Studien zur Nahrungskultur im 19./20. Jahrhundert)

Wir sind immer mittendrin? Transdisziplinarität in der feministischen Natur- und Technowissenschaftsforschung - Weber, Jutta; Saupe, Angelika (Dokumentation 29. Kongreß von Frauen in Naturwissenschaft und Technik)

„Ick kike in die Stern vndt versake Gott den herrn“. Versprachlichung des Teufelspaktes in westfälischen Verhörprotokollen des 16./17. Jahrhunderts. - Topalović, Elvira (Jahrbuch 20, Augustin Wibbelt-Gesellschaft e.V.)

Distributed algorithms for transmission power control in wireless sensor networks - Kubisch, Martin; Karl, Holger; Wolisz, Adam; Charlie Zhong, Lizhi; M. Rabaey, Jan (2003 IEEE Wireless Communications and Networking, WCNC 2003, New Orleans, LA, USA, 16-20 March, 2003)

A Subset Test for XPath Expressions under DTDs - Böttcher, Stefan; Steinmetz, Rita (20th British National Conference on Databases, BNCOD 20, Poster Papers)

Frauenberuf Sängerin. Ein Thema musikwissenschaftlicher Frauen- und Geschlechterforschung - Grotjahn, Rebecca (Rheinische Sängerinnen des 20. Jahrhunderts. Eine Dokumentation in Wort und Ton)

Many-body Coulomb effects in the optical properties of semiconductor heterostructures - Meier, Torsten; Pasenow, B.; Thomas, P.; Koch, S.W. (Germany NIC Series, Vol. 20)

Checking Behavioural Subtypes via Refinement - Wehrheim, Heike (Formal Methods for Open Object-Based Distributed Systems V, IFIP {TC6/WG6.1} Fifth International Conference on Formal Methods for Open Object-Based Distributed Systems {(FMOODS} 2002), March 20-22, 2002, Enschede, The Netherlands)

Use of PV Systems for Carbon Dioxide Reduction – a comparison of on- and off-grid systems in Brazil and Germany - Krauter, Stefan (Proceedings of the World Renewable Energy Congress VII, Köln (Deutschland), 29. Juni – 5. Juli 2002, (Buch mit CD) Pergamon Press)

Eletrificação rural através de sistemas fotovoltaicos autônomos: básicos, atividades no Brasil, aplicações, novos desenvolvimentos. (Ländliche Elektrifizierung mittels PV Systemen: Grundlagen, Beispiele, Aktivitäten in Brasilien, neue Entwicklungen) - Krauter, Stefan (Proceedings of 2º Fórum Energia Limpa, Rio de Janeiro (Brasilien), 29.–30. Juli 2002)

Eletrificação rural através de sistemas fotovoltaicos: básicos, atividades no Brasil, aplicações, desenvolvimentos atuais - Krauter, Stefan (3º Seminário Energia na Agricultura, Uberaba–MG (Brasilien). 27.–29. November 2002, S. III-1–9)

Sistema Solar Fotovoltaico Híbrido Integrado - Krauter, Stefan; Ochs, F. (3º Seminário Energia na Agricultura. Uberaba/MG (Brasilien). 27.–29. November 2002, S. III-10–17)

Moore, Gregory H., “Hilbert on the Infinite: The Role of Set Theory in the Evolution of Hilbert’s Thought”, In: Historia Mathematica 29 (2002), 40–64 - Peckhaus, Volker (Mathematical Reviews [)

Originalität als inszenierte Epigonalität. Christoph Martin Wieland zwischen Klassik, Aufklärung und Romantik - van Laak, Lothar (Akten des X. Internationalen Germanistenkongresses Wien 2000 “Zeitenwende – Die Germanistik auf dem Weg vom 20. ins 21. Jahrhundert”)

„Mouvance der Textsituation und des Textes (Heinrich von Morungen, MF 131, 25)“ - Egidi, Margreth (Akten des X. Internationalen Germanistenkongresses Wien 2000. „Zeitenwende – Die Germanistik auf dem Weg vom 20. ins 21. Jahrhundert“, unter Mitarbeit v. Hans Derkits, Bd. 5: Mediävistik und Kulturwissenschaften, betreut v. Horst Wenzel u. Alfred Ebenbauer; Mediävistik und Neue Philologie, betreut v. Ingrid Bennewitz, Werner Röcke u. Peter Strohschneider (Jahrbuch für Internationale Germanistik A, Kongressberichte 57))

Plädoyer für eine kontextsensitive Modellierung von Spracheinstellungen - Tophinke, Doris; Ziegler, Evelyn (Zeitenwende – Die Germanistik auf dem Weg vom 20. ins 21. Jahrhundert. Akten des X. Internationalen Germanistenkongresses Wien 2000. Bd. 3)

Vernunftkritik und biophile Begrifflichkeit. Französische Philosophie im 20. Jahrhundert - Hagengruber, Ruth Edith (Das Denken des Anderen)

Einleitung - Grotjahn, Rebecca; Hoffmann, Freia (Geschlechterpolaritäten in der Musikgeschichte des 18. bis 20. Jahrhunderts)

Geschlechterpolaritäten in der Musikgeschichte des 18. bis 20. Jahrhunderts

Architektonischer Wunschtraum, literarische Utopie, bauliche Realität. Samjatins “Wir” und die Architektur des 20. Jahrhunderts - Seng, Eva- Maria (Modell und Wirklichkeit, Festschrift zum 60. Geburtstag von Richard Saage)

Occlusion Culling for Virtual Environments based on the 3D-Sectorgraph - Klein, Jan; Fischer, Matthias (Proc. of 3. GI-Informatiktage 2001)
We present a new approximate occlusion-culling algorithm that in contrast to other algorithms, manages the objects of the scene in a 3D-sectorgraph. For generating a frame, as far as possible only the visible objects are rendered that can be found quickly by an edge of the graph. The algorithm allows a real-time navigation with over 20 frames per second in complex scenes consisting of over 10 millions of polygons. Moreover, approximation errors are very low.

Heiner Müller: Das eiserne Kreuz; Der Vater; Wüsten der Liebe - Eke, Norbert Otto (Reclams Romanlexikon. Bd. 5: 20. Jahrhundert III)

Herta Müller: Niederungen; Der Fuchs war damals schon der Jäger; Herztier - Eke, Norbert Otto (Reclams Romanlexikon. Bd. 5: 20. Jahrhundert III)

Behavioural Subtyping Relations for Object-Oriented Formalisms - Fischer, Clemens; Wehrheim, Heike (Algebraic Methodology and Software Technology. 8th International Conference, AMAST 2000, Iowa City, Iowa, USA, May 20-27, 2000, Proceedings)

Prosodic Cues at Speaker Turns - Mindt, Ilka (Corpus Linguistics and Linguistic Theory. Papers from the Twentieth International Conference on English Language Research on Computerized Corpora (ICAME 20))

Deutsche Dramatiker des 20. Jahrhunderts
2., kartonierte Auflage: Berlin 2002

Thomas Brasch - Eke, Norbert Otto (Deutsche Dramatiker des 20. Jahrhunderts)

George Tabori - Eke, Norbert Otto (Deutsche Dramatiker des 20. Jahrhunderts)

Helmut Obst: Apostel und Propheten der Neuzeit. Gründer christlicher Religionsgemeinschaften des 19. und 20. Jahrhunderts, Göttingen 2000 - Schroeter-Wittke, Harald (http://www.amazon.de)

Unterhaltung - Praktisch-theologische Exkursionen zum homiletischen und kultirellen Bibelgebrauch im 19. und 20. Jahrhundert anhand der Figur Elia - Schroeter-Wittke, Harald

Richard Beer-Hofmann: Der Tod Georgs - Eke, Norbert Otto (Reclams Romanlexikon. Bd. 3: 20. Jahrhundert I)

Data Abstraction for CSP-OZ - Wehrheim, Heike (FM'99 - Formal Methods, World Congress on Formal Methods in the Development of Computing Systems, Toulouse, France, September 20-24, 1999, Proceedings, Volume II)

Model-Checking CSP-OZ Specifications with FDR - Fischer, Clemens; Wehrheim, Heike (Integrated Formal Methods, Proceedings of the 1st International Conference on Integrated Formal Methods, IFM 99, York, UK, 28-29 June 1999)

Interkulturelle Bildung als Aufgabe haushaltsbezogenen Unterrichts - Schlegel-Matthies, Kirsten (Internationale Perspektiven in Hauswirtschaft und Haushaltswissenschaft. 20 Jahre Beirat. Dokumentations- und Diskussionsbeiträge)

Informatik '99: Informatik überwindet Grenzen. Tagungsband der 29. Jahrestagung der Gesellschaft für Informatik, Paderborn (Germany)

A study of broadcast news audio stream segmentation and segment clustering - Harris, Matthew J.; Aubert, Xavier L.; Haeb-Umbach, Reinhold; Beyerlein, Peter (Eurospeech)
In transcription of broadcast news, dividing the signal into homogeneous segments, and clustering together similar segments is important. Decoding a complete broadcast news program in one chunk is technically di cult. Also, through creation of homogeneous clusters of segments, improvement from adaptation can be increased. Two systems of segmentation and clustering are compared. The best system used the BIC algorithm to produce long, homogeneous segments, and a nearest neighbour bottom-up agglomerative clustering algorithm to produce homogeneous clusters. Adaptation brought a word error rate (WER) improvement from 23:4% to 21:0% using the automatic segmentation and clustering, compared to an improvement from 21:8% to 20:0% using a handmade \correct" segmentation and clustering.

19th Century Logic: Between Philosophy and Mathematics - Peckhaus, Volker (Proceedings of the Canadian Society for the History and Philosophy of Mathematics. Société Canadienne d’Histoire et Philosophie des Mathématiques, Bd. 11: Twenty-Fourth Annual Meeting. University of Ottawa. Ottawa, Ontario, May 29–31, 1998)

Gunter Scholtz (Hrsg.): Historismus am Ende des 20. Jahrhunderts. Eine Internationale Diskussion. Akademie-Verlag, Berlin 1997 - Peckhaus, Volker (Philosophischer Literaturanzeiger)

On Deepening Foundations: Hilbert’s Axiomatic Program between Pragmatics and Naturalism [Abstract] - Peckhaus, Volker (International Union of History and Philosophy of Science. 11th International Congress of Logic, Methodology and Philosophy of Science. Volume of Abstracts. August 20–26, 1999, Cracow, Poland)

Polarization mode dispersion compensation at 10, 20, and 40 Gb/s with various optical equalizers - Noé, Reinhold; Sandel, D; Yoshida-Dierolf, M; Hinz, S; Mirvoda, V; Schopflin, A; Glingener, C; Gottwald, E; Scheerer, C; Fischer, G; Weyrauch, T; Haase, W (JOURNAL OF LIGHTWAVE TECHNOLOGY)

Polarization mode dispersion compensation at 10, 20, and 40 Gb/s with various optical equalizers - Noé, Reinhold; Sandel, D; Yoshida-Dierolf, M; Hinz, S; Mirvoda, V; Schopflin, A; Glingener, C; Gottwald, E; Scheerer, C; Fischer, G; Weyrauch, T; Haase, W (JOURNAL OF LIGHTWAVE TECHNOLOGY)

Semi-Formal and Formal Specification Techniques
During the last 20 years several different formal and semi-formal specification techniques have been successfully developed and used. Applications comprise the specification of simple programs, data types and processes as well as complex hardware and software systems. The variety of specification techniques ranges from formal set theoretical, algebraic, and logic approaches for specifying sequential systems and from Petri-nets, process algebras, automata, and graph grammars for specifying concurrent and distributed behaviors to semi-formal software engineering methods for developing complex systems. Formal and semi-formal approaches have their advantages and disadvantages: the informal diagrammatic methods are easier to understand and to apply but they can be ambiguous. Due to the different nature of the employed diagrams and descriptions it is often difficult to get a comprehensive view of all functional and dynamic properties. On the other hand, the formal approaches are more difficult to learn and require mathematical training. But they provide mathematical rigor for analysis and prototyping of designs. Verification is possible only with formal techniques. Since a few years many researchers and research groups are putting more and more effort in closing this gap by integrating semi-formal and formal specification techniques. Their studies and experiences show the added value of combining semi-formal and formal techniques and at the same time open a whole range of new problems and questions which cannot be asked when studying formalisms in isolation. In this seminar more than 40 scientists came together in 28 talks and two panel discussions to study possibilities and solutions for integrating and validating different formal and semi-formal specification techniques. Similarities and differences of formal and semi-formal specification formalisms as well as possibilities for combining such techniques were discussed. Most talks of this seminar analysed, compared, or integrated at least two such methods. On behalf of all participants the organizers would like to thank the staff of Schloss Dagstuhl for providing an excellent environment to the conference. The support of the TMR programme of the European Community is gratefully acknowledged. Due to this programme it was possible to fund the participation of several young researchers and of three key note speakers.

Klassische philosophische Texte von Frauen. 2nd ed

Spalt, Detlef D., „Exaktheit als Konstante, Begriffe im Wandel des mathematischen Denkens. Zur Analysis im 19. und 20. Jahrhundert“, in: Czermak (Hg.) 1993 [Zbl 0836.00022], 45–59 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Fiber-based distributed PMD compensation at 20 Gb/s - Noé, Reinhold; Sandel, D; Yoshida-Dierolf, M; Hinz, S; Glingener, C; Scheerer, C; Schopflin, A; Fischer, G (24TH EUROPEAN CONFERENCE ON OPTICAL COMMUNICATION, VOL 1-3: VOL 1: REGULAR AND INVITED PAPERS; VOL 2: TUTORIALS AND SYMPOSIUM PAPERS; VOL 3: POSTDEADLINE PAPERS)

Dependency-Based Action Refinement - Rensink, Arend; Wehrheim, Heike (Mathematical Foundations of Computer Science 1997, 22nd International Symposium, MFCS'97, Bratislava, Slovakia, August 25-29, 1997, Proceedings)

Dependency-Based Action Refinement - Rensink, Arend; Wehrheim, Heike (Mathematical Foundations of Computer Science 1997, 22nd International Symposium, MFCS'97, Bratislava, Slovakia, August 25-29, 1997, Proceedings)

Logik, Mathesis universalis und allgemeine Wissenschaft. Leibniz und die Wiederentdeckung der formalen Logik im 19. Jahrhundert - Peckhaus, Volker
Rezensionen: J. Legris, “Mathesis Universalis”, Mathesis 13 (1997), 167– 175; Zbl. Math. 884.01021 (R. Murawski); Philosophischer Literaturanzeiger 51 (1998), 114–117 (G. Schenk); MR 98h:01013 (H. Sinaceur); Peirce Project Newsletter 3 No. 1, 7; Philosophiegeschichte und logische Analyse. Logical Analysis and History of Philosophy, Bd. 2, Mentis: Paderborn 1999, 259–264 (W. Malzkorn); History and Philosophy of Logic 20 (1999), 67–69 (H. Linneweber-Lammerskitten); Erkenntnis 50 (1999), 133–136 (P. Mancosu); Berichte zur Wissenschaftsgeschichte 22 (1999), 207–208 (P. Mancosu); NTM. Schriftenreihe für Geschichte der Naturwissenschaften, Technik und Medizin N.S. 8 (2000), H. 1, 290 (K.-H. Schlote), 49–50; Anuario Filosofico 32 (1999), 853–854; M.F., “La logica di Leibniz nel XIX secolo”, Giornale critico della filosofia Italiana 6 ser. 20 (2000), 161–164; Archiv für Geschichte der Philosophie 82 (2000), 349–352 (R. Vilkko); Epistemologia 24 (2001), 152–155 (M. Ferriani); The Review of Modern Logic 9, nos. 3 & 4 (2003–2004), 119–122 (H. Frank).